2006
DOI: 10.1074/jbc.m508485200
|View full text |Cite
|
Sign up to set email alerts
|

Rational Development of β-Peptide Inhibitors of Human Cytomegalovirus Entry

Abstract: Human cytomegalovirus (HCMV) is a pervasive and significant pathogen. At present, there is no HCMV vaccine, and the available drugs target only replication events. Thus, new therapeutic strategies are needed. HCMV fusion appears to require interactions of ␣-helical regions in viral surface glycoproteins gB and gH. Oligomers of ␤-amino acids ("␤-peptides") are attractive unnatural scaffolds for mimicry of specific protein surfaces, because ␤-peptides adopt predictable helical conformations and resist proteolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 42 publications
(47 reference statements)
0
66
1
Order By: Relevance
“…The results reported here represent a substantial advance relative to earlier efforts to develop unnatural oligomers that mimic ␣-helices involved in protein-protein recognition events (13,14,28,(41)(42)(43)(44)(45)(46). Previous work has been limited to relatively short ␣-helical targets, typically only two to four helical turns.…”
Section: Discussionmentioning
confidence: 76%
“…The results reported here represent a substantial advance relative to earlier efforts to develop unnatural oligomers that mimic ␣-helices involved in protein-protein recognition events (13,14,28,(41)(42)(43)(44)(45)(46). Previous work has been limited to relatively short ␣-helical targets, typically only two to four helical turns.…”
Section: Discussionmentioning
confidence: 76%
“…A ␤-peptide that does not block HCMV infection was used as a control. The inhibitory ␤-peptide displays a high degree of specificity for HCMV, as it does not block entry of mouse CMV or HSV-1 (57). Pretreatment of cells with gB-DLD resulted in a 92% decrease in virus infection as assessed by the HCMV-IE2 GFP reporter virus (Fig.…”
Section: Hcmv Entry Inhibitors Block Hcmv-induced Ifn Signaling But Nmentioning
confidence: 99%
“…The anti-P56 Ab was a gift from G. Sen (The Cleveland Clinic Foundation, Cleveland, OH) (56). The second generation ␤-peptide 19, a potent inhibitor of HCMV entry (57), is designated ␤-peptide (ϩ) in this study, and a control ␤-peptide that does not block HCMV entry is designated ␤-peptide (Ϫ).…”
Section: Reagents and Absmentioning
confidence: 99%
“…21,22,24 Larger mixedsequence peptides containing both α-and β-amino acids have also shown success as protein ligands for the BH3 recognition site of Bcl-x L . 25,26 Several strategies have been pursued to identify β-peptides that assemble into discrete, wellfolded quaternary structures whose thermodynamic properties resemble those of natural proteins. Remarkably, as early as 1998, Clark et al showed that cyclic β 3 -peptides designed to self-assemble in lipid bilayers supported K + conductance, although the existence of higherorder structure was not investigated.…”
Section: Introductionmentioning
confidence: 99%